SYNTHESIS AND ESTIMATION OF TOTAL EXTRACELLULAR PROTEIN CONTENT IN BACILLUS SUBTILIS UNDER MILD STRESS CONDITION OF CERTAIN ANTIMICROBIALS - A, KHUSRO; D, Sankari (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The present study was investigated to determine the impact of certain antimicrobials on a novel bacterial isolate for the estimation of total extracellular protein. Methods: In this regard, isolation and molecular characterization of the isolate from poultry farm feces soil sample was done by serial dilution, followed by morphological characteristics and biochemical tests of pure isolated culture. Further, the identification of bacterium as Bacillus subtilis strain KPA was confirmed by subjecting its amplicon (483 bp) to 16S rRNA gene sequence analysis and pairwise alignment through basic local alignment search tool. Different volumes of antimicrobial agents such as Allium sativum, ampicillin and mercuric chloride at their sub-minimal inhibitory concentration (MIC) values were added to the lag phase culture of strain KPA. Total extracellular protein estimation was done through Bradford test. Partially purified extracellular proteins were observed as spots through thin layer chromatography (TLC). Results: The total extracellular protein content in strain KPA was found to be enhanced after 48 hrs of incubation in presence of antimicrobials tested here. Mercuric chloride was able to enhance total protein in the bacteria even after 24 hrs of incubation. Separation of partially purified extracellular proteins of treated samples by TLC was observed as different spots with different retention factor values, compared with non-treated or control sample. Conclusion: The stress response is a metabolic program activated due to unfavorable conditions. Hence, B. subtilis strain KPA in the presence of sub- MIC of A. sativum, ampicillin and mercuric chloride could regulate bioactive proteins production. Keywords: Antimicrobials, Bacillus subtilis, Sub-minimal inhibitory concentration, Total protein, Thin layer chromatography.